CODE SWITCHING IN BILINGUAL CLASSROOM - Rakhmat Wahyudin Sagala; Bambang Panca Syahputra (Jurnal Serunai Bahasa Inggris, 2019)
Nowadays, universal language which is used in the world is English. The ability of speaking English is being a prerequisite to be someone’s success in the future. The aim of this study is to find the phenomenon of code switching in bilingual classroom which focused on types of grammatical code switching and reasons of using grammatical code switching. This research applied descriptive qualitative research which obtained the data from the discourse of lecturers and students in bilingual classroom at Universitas Negeri Medan. The researchers applied observation, interview and documentation. The data showed that lecturers and students used grammatical code switching in the classroom such as 2 tag code switching, 12 inter-sentential code switching, 22 intra-sentential code switching, 3 proper nouns, 1 negative words, 8 similarity of words in languages and 3 discourse marker. There are some reasons why the participants used code switching in their discourse. First, code switching made students more understand what the lecturers explained because not all bilingual students are able to speak English. Second, they used code switching because lack of vocabulary in English and so that they switched languages to make the material were easier to be understood.Keywords— Code Switching, Types of Grammatical Code Switching, Reasons of Code Switching, Bilingual Education